A B2N monolayer: a direct band gap semiconductor with high and highly anisotropic carrier mobility. Issue 3 (6th January 2022) - Lin, Shuyi; Guo, Yu; Xu, Meiling; Zhao, Jijun; Liang, Yiwei; Yuan, Xuanhao; Zhang, Yiming; Wang, Feilong; Hao, Jian; Li, Yinwei
Abstract : A planar 2D B2 N monolayer with a desirable direct band gap, high thermal stability, and high and highly anisotropic carrier mobility is shown to be a promising functional material for nanoelectronics and optoelectronics applications. Abstract : Two-dimensional materials with a planar lattice, suitable direct band gap, and high and highly anisotropic carrier mobility are desirable for the development of advanced field-effect transistors. Here we predict three thermodynamically stable B-rich 2D B–N compounds with the stoichiometries of B2 N, B3 N, and B4 N using a combination of crystal structure searches and first-principles calculations. Among them, B2 N has an ultraflat surface and consists of eight-membered B6 N2 and pentagonal B3 N2 rings. The eight-membered B6 N2 rings are linked to each other through both edge-sharing (in the y direction) and bridging B3 N2 pentagons (in the x direction). B2 N is a semiconductor with a direct band gap of 1.96 eV, and the nature of the direct band gap is well preserved in bilayer B2 N. The hole mobility of B2 N is as high as 0.6 × 10 3 cm 2 V −1 s −1 along the y direction, 7.5 times that in the x direction. These combined novel properties render the B2 N monolayer as a natural example in the field of two-dimensional functional materials with broad application potential for use in field-effect transistors.